Error médico auto percibido durante el proceso formativo docente-asistencial de estudiantes de internado médico en México - Mendoza-González, Mauricio Fidel; Vázquez-Martínez, Francisco Domingo; Luzanía Valerio, Manuel Salvador (UVserva, 2024)
El objetivo del estudio fue estimar las diferencias de exposición a factores de riesgo y de protección que ayuden a explicar el error médico auto percibido en el espacio docente asistencial en médicos internos de pregrado durante el periodo 2019 – 2021 en el estado de Veracruz, México. Se realizó un estudio transversal en el que se emplearon bases de datos de médicos internos adscritos a unidades hospitalarias en el estado de Veracruz, en los años 2020, 2021 y 2022, bajo la responsabilidad académica de la Universidad Veracruzana y las instituciones de salud receptoras de estudiantes de medicina en el estado de Veracruz en México. Se obtuvo información de 679 médicos internos de pregrado. El índice de tutoría académica se situó en 62.6% y en 74.1 % el índice de prevención del error médico, ligeramente superiores en las mujeres. La evaluación analítica bivariada de factores de riesgo que explican el error médico auto percibido en los médicos internos centra los valores con significancia estadística en aquellas condiciones que corresponden esencialmente a las decisiones autónomas, el trato, la comunicación o la seguridad. Dicho riesgo al error se incrementó en más de cinco veces al tomar decisiones clínicas autónomas. Self-perceived medical error during the teaching-care training process of medical internship students in Mexico Abstract: The objective of the study was to estimate the differences in exposure to risk and protective factors that provide information to explain self-perceived medical error in the teaching-care space of medical internship students in the state of Veracruz, Mexico. A long-term cross-sectional study was carried out using information obtained from the Observatory of Medical Education and Human Rights (OBEME) of the Universidad Veracruzana (UV), from doctors assigned to hospital units in the state of Veracruz, in the years 2020, 2021 and 2022, under the academic responsibility of the UV and the health institutions receiving medical students in the state of Veracruz, in Mexico. Information was obtained from 679 undergraduate interns. An academic tutoring and supervision index (ITSA) was constructed that stood at 62.6 %, which was considered not to have reached a satisfactory value to prevent medical error, and a medical error prevention index (IPE-Med) at 74.1 %, which was on the limit of being sufficient to meet its goal, with slightly higher values in women and therefore more satisfactory. The analytical evaluation of risk factors that explain self-perceived medical error in internal physicians focuses values with statistical significance on those conditions that essentially correspond to autonomous decisions, treatment, communication, or safety. This risk of error increased more than five times when making autonomous clinical decisions.